The Secret Life of the PERIODIC TABLE : Unlocking the mysteries of all 118 elements - Still, Ben Dr.; Susanna Geoghegan Gift Publishing (London : Cassell, 2016)
"This book uncovers the fascinating stories behind the formulation of the periodic table and describes by who and how the 118 elements were discovered. The reader is able to gain a basic understanding of the fundamentals of atomic science with the help of fascinating trivia to keep the content interesting"--Provided by publisher.
Includes index
Keywords: Periodic table of the elements -- Popular works; Periodic law -- Popular works; Chemical elements -- Popular works; Popular works